Eficiencia en la administración de minerales previo a la utilización de un protocolo de sincronización de celo en vacas Brown- Swiss en el cantón Pallatanga - Chávez Gaguancela, Luis Aníbal (2025)
The Cattle production in the Pallatanga canton faces challenges in reproductive efficiency, with nutrition being a key factor. Estrus synchronization, a valuable biotechnological tool, can enhance this efficiency, but its success largely depends on the animals' nutritional status. Deficiencies in essential minerals can negatively affect oocyte quality, endometrial function, and immune response, compromising fertility. Therefore, mineral supplementation, particularly parenteral route administration, emerges as a promising strategy to optimize reproductive function. The research aimed to evaluate the efficiency of parenteral mineral supplementation on ovarian activity prior to the implementation of an estrus synchronization protocol in Brown Swiss cows in the Pallatanga canton, was conducted on 30, divided into three groups of 10 individuals. The first and second groups received parenteral mineral supplementation before the synchronization protocol, while the third group served as the control group. The study which used descriptive statistics and the application of the parametric ANOVA test and Tukey’s test for group comparisons. The study revealed significant differences in the ovarian activity of Brown Swiss cows treated with minerals compared to the control group. Although no differences in follicle size were observed at the beginning of the study (day 0), from day 8 to day 16, treated cows showed significantly greater follicular development (p<0.0001). Similarly, the size of the corpus luteum, an indicator of ovarian function and potential fertility, was significantly larger (p<0.0001) in cows that received mineral supplementation. Additionally, significant differences were found in estrus expression (p=0.0067) between the treatment groups and the control group, suggesting that mineral administration may have also influenced the manifestation of estrus in the cows. The administration of minerals prior to estrus synchronization had a positive effect on follicular dynamics, corpus luteum size, and estrus expression. These findings could have important practical implications for improving the efficiency of reproductive programs in this breed and region.